IMPROVING INDONESIA'S HUMAN RESOURCES QUALITY TO SUPPORT NATIONAL DEFENSE: LESSON LEARNED FROM SOUTH KOREA - M. Prakoso Aji (Indonesia Defense University, 2020)
The success of South Korea in developing its country, especially after the Korean War in the 1950s, has fascinated the world. A country that was once considered poor and divided north and south after the war, turned into a country that should be respected internationally. The success of this country in carrying out social-political reforms made the policies carried out by the government succeed. Strengthening the industrial sector in its economic activities has yielded extraordinary benefits. Cultural diplomacy made by the government, make Korean culture known and liked by people in almost every part of the world. Economic increase and the appropriate policy choices, advancing the field of education and research in the country. The development of education and research makes the country's defense sector stronger. The success of the domestic defense industry to meet the needs of domestic defense equipment makes the country able to withstand threats from North Korea, even able to become an exporter of defense equipment. The purpose of this article is to see how Indonesia can learn from South Korea, especially from the social-political, economic, cultural, educational and research fields, and also defense. This was done in order to be able to improve the quality of Indonesia's human resources to support national defense. The results of this study indicate that to improve the quality of Indonesian human resources in the field of defense, Indonesia can learn not only from the South Korean defense field, but also in the fields of social politics, economics, culture, as well as education and research.Keywords: konfusianism, Industrialization, Hallyu, Research and Development, and Defense Industry